Cross-border bank flows, regional household credit booms, and bank risk-taking - Dominik Boddin; Daniel Marcel te Kaat; Kasper Roszbach (Asian Development Bank (ADB), 2025)
This paper provides novel microlevel evidence that cross-border bank flows are an important means for households to access credit, not only in emerging markets but also in advanced economies. Using supervisory bank-level data alongside household credit and consumption data from Germany, we study how lending to households was impacted by the influx of cross-border bank funding following the European Central Bank's implementation of nonconventional monetary policy in 2014 and 2015. Regional banks that were highly exposed to fluctuations in foreign capital inflows increased consumer lending to riskier, lower-income households by 50% more than other banks. Rising deposit inflows from non-euro area banks induced less-capitalized banks to expand their lending on the extensive margin. The analysis concludes that Improved access to credit enables lower-income customers of exposed banks to increase nondurable consumer spending. Data from a larger group of euro area countries confirm that conclusion.
Keywords: F3; G2; G5; 330; cross-border bank flows; households; bank lending; risk-taking; credit booms; funding shocks